The Utility of Myeloperoxidase Immunostaining to Characterize Immune Deposits in Patients With Crescentic Glomerulonephritis - Rachelle Gietzen; Tiffany N. Caza; Alejandro Best-Rocha; Christopher P. Larsen (Kidney International Reports)
Introduction: Pauci-immune crescentic glomerulonephritis (GN) is nearly synonymous with antineutrophil cytoplasmic antibody (ANCA)–associated disease. Cases with immune complex deposition create a diagnostic conundrum leading to suspicion for concurrent infection or autoimmune disease. Small case series have demonstrated myeloperoxidase (MPO) in the immune deposits in patients with membranous nephropathy (MN) and ANCA-associated disease. However, the specificity of MPO staining to characterize immune deposits in crescentic GN has not been thoroughly evaluated. Methods: We performed MPO immunostaining of 143 kidney biopsies, including pauci-immune crescentic GN (n = 15), ANCA with immune-complex crescentic GN (n = 20), MN without crescents (n = 24), endocarditis-associated crescentic GN (n = 25), hydralazine-associated crescentic GN (n = 11), and concurrent crescentic GN and MN without phospholipase A2 receptor (PLA2R) (n = 38) and with PLA2R (n = 10). MPO immunohistochemistry (IHC) was evaluated for positivity, character, and location of MPO immune deposits by 4 blinded pathologists. Results: In patients with dual crescentic GN and MN without PLA2R, 84.2% were MPO-IHC positive. Crescentic GN with mesangial IgG was MPO-IHC positive in 40%. Crescentic GN related to hydralazine exposure was MPO-IHC positive in 72.7%. All cases with pauci-immune crescentic GN, endocarditis-associated cases, and MN cases with known antigens were negative for MPO. Conclusion: Our study demonstrated that glomerular immune deposits in patients with crescentic GN with positive MPO serology demonstrated MPO positivity in the pattern of immune deposits in the majority of cases. Glomerular immune complexes in patients with MPO-positive crescentic GN therefore represent MPO-IgG immune complexes and should be thought of as one disease rather than a second disease process.